Theoretical Foundations of Drama-Based Instruction in Developing EFL Learners’ Speaking Fluency - Zikriyoyeva Shakhzoda (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This comprehensive research paper conducts a rigorous exploration of the historical, theoretical frameworks and pedagogical significance of drama-based instruction (DBI) in enhancing English as a Foreign Language (EFL) learners' speaking fluency. Drawing extensively upon second language acquisition (SLA) theories, communicative language teaching (CLT), experiential learning models, and psychological coping mechanisms, this article synthesizes how dramatic activities reduce affective filters and promote communicative competence. Spanning the critical analysis of pedagogical traditions, the paper establishes a detailed taxonomy of drama techniques—including role-plays, simulations, and improvisations—and analyzes their cognitive, social, and emotional impacts on students within technical higher education institutions. Finally, the research maps out structured procedural implementations and delivers an objective evaluation rubric designed to track long-term oral proficiency development.